2022
DOI: 10.21203/rs.3.rs-1848919/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The rapid change of mental health in college students after on-campus quarantine in Shanghai 2022 Covid lockdown

Abstract: Importance: Social isolation during outbreaks of epidemics always challenge psychological resilience profoundly. However, it still remains unclear how students’ mental health would be affected by strict on-campus quarantine, which means students stayed at dormitories or on-campus for quarantine. We analyzed the data from one of the earliest universities releasing strict on-campus quarantine to prevent the Omicron spread-out in Shanghai, to evaluate the time course of the psychological resilience in the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…Wang et al ( 16 ) and Du et al ( 19 ) found a significant increase in the rate of depression in Chinese adolescents and adults, respectively. For Chinese students, COVID-19 on-campus quarantine increased diagnoses of depression from 9.1 to 36.1% ( 20 ). The rapid growth of psychological diseases such as depression caused by the COVID-19 lockdown or quarantine has become a common problem globally.…”
Section: Covid-19 Lockdown In China and The Magnified Risk Of Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al ( 16 ) and Du et al ( 19 ) found a significant increase in the rate of depression in Chinese adolescents and adults, respectively. For Chinese students, COVID-19 on-campus quarantine increased diagnoses of depression from 9.1 to 36.1% ( 20 ). The rapid growth of psychological diseases such as depression caused by the COVID-19 lockdown or quarantine has become a common problem globally.…”
Section: Covid-19 Lockdown In China and The Magnified Risk Of Depressionmentioning
confidence: 99%
“…This conclusion has been reflected in multinational data. For instance, Khubchandani et al (17) found an increased rate of depression and anxiety after the COVID-19 lockdowns in the USA; Schwinger et al (18) (20). The rapid growth of psychological diseases such as depression caused by the COVID-19 lockdown or quarantine has become a common problem globally.…”
Section: Introductionmentioning
confidence: 99%